2015
DOI: 10.14303/ajfst.2015.045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dryer parameters on the drying characteristics and quality of cassava flour

Abstract: In this study a conductive rotary dryer (CRD) was developed for the drying of pulverized cassava meal with a view to mechanizing the traditional sun-drying method. The effects of four parameters of the dryer were investigated and optimized using the Taguchi technique. Drum temperature had the most significant effect on the swelling index of the cassava meal with signal-to-noise ratio difference of 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
2
0
1
Order By: Relevance
“…Observations from the results obtained show that the elimination of the cyanide level was greatly affected by the duration of drying of the cassava chips in the sun drying method. As the duration of drying increased, the cyanide contents of the samples also decreased steadily similar to the recommended standard of 0.01 mg/g [26], except samples D and E which had the final cyanide contents of (0.01589 mg/g and 0.00728 mg/g) respectively which were a little different from the recommended standard and could be attributed to the maximum (0.08980 mg/g) and minimum (0.02350 mg/g) cyanide contents the cultivars initially contained respectively. In addition, a close inspection of the graphs a similar trend in all the sample's cyanide contents except for sample D results which tends to be a little higher, reasons which could be aligned to the highest initial cyanide content (0.08980 mg/g).…”
Section: Effect Of Duration On Cyanidesupporting
confidence: 65%
“…Observations from the results obtained show that the elimination of the cyanide level was greatly affected by the duration of drying of the cassava chips in the sun drying method. As the duration of drying increased, the cyanide contents of the samples also decreased steadily similar to the recommended standard of 0.01 mg/g [26], except samples D and E which had the final cyanide contents of (0.01589 mg/g and 0.00728 mg/g) respectively which were a little different from the recommended standard and could be attributed to the maximum (0.08980 mg/g) and minimum (0.02350 mg/g) cyanide contents the cultivars initially contained respectively. In addition, a close inspection of the graphs a similar trend in all the sample's cyanide contents except for sample D results which tends to be a little higher, reasons which could be aligned to the highest initial cyanide content (0.08980 mg/g).…”
Section: Effect Of Duration On Cyanidesupporting
confidence: 65%
“…Mechanical dewatering is combined with the thermal drying of BSG to achieve such moisture contents. Industrial dryers include steam tube, flash type, rotary drum or disk dryers, with direct or indirect heating with superheated steam (Ström, no date;Stroem, Desai and Hoadley, 2009;Aboltins and Palabinskis, 2015;Romdhana, Bonazzi and Esteban-Decloux, 2015;Sanni and Fakunle, 2016). Rotary drums to dry BSG reported require between 1.2 to 1.5 tonne steam per 1 tonne wet BSG .…”
Section: Preservation and Drying Of Bsgmentioning
confidence: 99%
“…Replacement or substituting wheat flour with flour from other sources can increase the utilization of native plants and contribute to lowering the cost of the product [15]. Several studies have been reported on the use of composite flour in producing bread, biscuits and noodles [16][17]. Adding cassava flour with a low protein content in wheat flour will reduce the percentage of protein in composite flour.…”
Section: Introductionmentioning
confidence: 99%